Student-centered learning in an engineering course with project-integrated laboratory experiment - Jennifer Leijon; Kjell Staffas; Cecilia Boström; Hans Bernhoff (Högre Utbildning, 2020)
In this paper we discuss and present results from the pedagogical development of an advanced-level undergraduate electrical engineering course at Uppsala University, where a new laboratory experiment was implemented. The implementation of the laboratory experiment seemed to result in improved student performance on written tests and a better overall success/pass rate when compared with previous years. The aim of this paper is to describe the course development and its outcome, with a focus on the individual engineering laboratory experiment. We conclude that unique student tasks, connected to realistic engineering problems, may increase the engagement and subject understanding of students.